Quality Assuring Teaching and Learning Processes in Higher Education: A Critical Appraisal - Netshifhefhe, Lufuno; Nobongoza, Vakele; Maphosa, Cosmas (Communication, 2016)
Universities, the world over, seek excellence in teaching and learning. Emphasis is put on quality of all university processes as universities seek to satisfy major stakeholders. Quality assurance of teaching and learning processes and procedures is important in order to ensure that relevant and useful graduates are produced from universities. In the concept paper the researchers explore the concepts quality and quality assurance. A link is drawn between quality assurance and teaching and learning processes in higher education. Theories underpinning quality assurance in higher education are explored, importance of quality assurance is examined and the different dimensions quality assurance could take in teaching and learning are discussed. The researchers further discuss challenges associated with quality assurance in higher education, draw conclusions and make recommendations towards quality enhancement in university teaching and learning processes.
Published Article
Keywords: Accountability; Feedback; Quality Enhancement Teaching Processes; Tertiary Institutions